Changes in the relationship between ENSO and the East Asian winter monsoon under global warming - Zixuan Jia; Massimo A Bollasina; Chaofan Li; Ruth Doherty; Oliver Wild (Environmental Research Letters, 2020)
Changes in the relationship between El Niño-Southern Oscillation (ENSO) and the East Asian winter monsoon (EAWM) at various global warming levels during the 21st century are examined using the Max Planck Institute Grand Ensemble Representative Concentration Pathway 8.5 experiments. The externally forced component of this relationship (i.e. forced by greenhouse gases and anthropogenic aerosols emissions) strengthens from present-day to +1.5 °C, and then weakens until +3 °C. These changes are characterized by variations in strength and location of the core of El Niño-related warming and associated deep convection anomalies over the equatorial Pacific leading to circulation anomalies across the Asian-Pacific region. Under global warming, the ENSO–EAWM relationship is strongly related to the background mean state of both the EAWM and ENSO, through changes in the EAWM strength and the shift of the ENSO pattern. Anthropogenic aerosols play a key role in influencing the ENSO–EAWM relationship under moderate warming (up to 1.5 °C).